Interação entre a sociedade e dados abertos: o que revelam os planos de dados abertos das universidades federais - Gaffrée, João Roberto de Lima (2020)
Open Government Data consists of public information, which are available on the internet. It represents a theme that over the years appears more frequently in research and other debates in society. This work had as a general objective to identify which role is reserved for society actors in the open data plans, of the Federal Universities of Brazil. It seeks to contribute to fill a gap in the theme, which is to understand how relations between governments and societies are exercised. As a research context, the open data plans of federal Universities were used, as they recognize the importance of these organizations (government) in the function of promoting greater knowledge, technology, innovation and interaction between these themes and society. The study was characterized in a descriptive and documentary research, with the collection of data based on documents, secondary data, such as open data plans. The research approach is qualitative, because it was used to interpret the content of the documents. Regarding data analysis, we opted for content analysis, in documents. As a result, we highlight the following: society actors are of great importance when it comes to motivations and criteria to promote data opening / publication; low importance in actions or activities aimed at the use / reuse of this data. There is a great concern with legal and technical aspects, on the part of Universities, in this process of opening data. Universities do not use a possible potential among their expertise, as example, courses and other areas within the process of opening data.